Determination of the thermal protective performance of clothing during bench-scale fire test and flame engulfment test: Evidence from a new index. (May 2015) - He, Jiazhen; Wang, Min; Li, Jun
The protective performance of heat- and flame-resistant materials can be studied using a bench-scale test or a full-scale instrumented manikin test. However, there are some limitations of these evaluation methods. The existing bench-scale test could not be applied entirely to assess the thermal protective performance of fabrics if the exposure duration is fixed, while the existing manikin test only provides limited information about the local difference in thermal insulation. This study developed a new index of maximum attenuation factor to second-degree burn injury (maximum attenuation factor) as an improved quantitative method of the thermal protective performance, and then investigated the use of maximum attenuation factor during the bench-scale test as well as the manikin test. It demonstrated that the calculations of maximum attenuation factor were highly repeatable. In both the bench-scale and the manikin test, strong correlations were found between the results derived from the proposed method and the measurements from the existing test method. The results between the bench-scale test and the manikin test can also be compared as a united index.